Geochemical Signatures of Major Elements in Shintaku Granitic Rocks - E.C. Chukwu; B.N. Ekwueme; C.J. Hetherington; K. Werts; A. C. Ugwu; I. Agbi (Academia Open, 2025)
General Background This study examines the geochemical behavior of granitic rocks in the Shintaku area, a region within the Nigerian Basement Complex where magmatic evolution remains debated due to limited integrated structural–geochemical data. Specific Background Earlier works suggest that Pan-African tectonism produced heterogeneous magmas in southwest Lokoja, yet the mechanisms generating the acidic and intermediate intrusive rocks in this locality are still insufficiently constrained. Knowledge Gap Despite numerous metamorphic studies, the petrogenesis and geochemical pathways of the granitic bodies in southeastern Lokoja have not been comprehensively analyzed using modern analytical techniques. Aims This research investigates magma sources, fractionation trends, and alumina saturation indices to reconstruct the magmatic evolution of the Shintaku granites. Results Major element compositions show enrichment in SiO2, Al2O3, and alkalis, with smooth Harker trends implying fractional crystallization, while rough trends indicate partial melting and magma mixing. The coexistence of metaluminous and peraluminous signatures, along with subalkaline affinities, supports heterogeneous mantle–crust melt interaction. Novelty This study provides the first integrated petrographic and geochemical characterization of the Shintaku granites using XRF, SEM, and LA-ICP-MS datasets. Implications Findings refine the petrogenetic model of southeastern Lokoja and offer a stronger basis for assessing mineralization potential and regional tectonomagmatic evolution.Highlight : Highlights major compositional variations that reflect the influence of magma fractionation. Emphasizes evidence of partial melting and magma mixing as drivers of magma heterogeneity. Confirms the S-type granitoid character linked to peraluminous supracrustal sources. Keywords : Granitic Rocks, Magmatic Fractionation, Fractional Crystallization, Partial Melting, Magma Mixing